Situating A Dictionary of South African English on Historical Principles within a More Comprehensive Lexicographic Process - Gouws, Rufus H. (Lexikos, 1999)
South African English can be regarded as a fully-fledged variety of English which qualifies for comprehensive lexicographic treatment. This paper focuses on the presentation and treatment of South African English in A Dictionary of South African English on Historical Principles. The structure of this dictionary as a carrier of texts and the way in which the editors adhere to current metalexicographic guidelines are discussed. This paper also situates the dictionary and its contribution within the broader South African lexicographic endeavour. Reference is made to other South African dictionaries in order to identify the position of this dictionary within the South African dictionary family.